Soil quality assessment of Pokkali lands (AEU 5) in the post (2018) flood scenario of Kerala - Unni, Neha; A. K., Sreelatha (Journal of Tropical Agriculture, 2021)
Kerala state witnessed large scale devastating flood in August 2018 due to intensive rainfall, causing significant damage to the agricultural sector and human life. One of the most affected districts was Ernakulam, especially Pokkali lands, agro ecological unit 5 (AEU 5). Pokkali lands represent the lowlands, often below sea level, in coastal areas of Ernakulam district and extending to parts of Thrissur and Alappuzha districts. The soils are hydromorphic, often underlain by potential acid-sulphate sediments with unique hydrological conditions. The study was undertaken to assess the soil quality in the post flood scenario of AEU 5. Initial survey was conducted and fifteen severely flood affected panchayats were selected. Geo-referenced composite soil samples were collected from these panchayats and were characterized for physical, chemical and biological properties. From these data, minimum data set (MDS) which highly influenced the soil quality was developed which included available Mg, pH, porosity, available Mn, organic carbon, microbial biomass carbon, available Cu and Fe. The highest soil quality index mean was observed in Chendamangalam (0.70). Based on the relative soil quality index values the panchayats were categorized into three groups, i.e., poor, medium and good. Out of 15 panchayats 10 were listed under poor category and 5 under medium category. Four panchayats showed decrease in soil quality on comparison with pre flood data.